ANALISIS PENERAPAN AKUNTANSI SYARIAH SISTEM BAGI HASIL DALAM PROGRAM TABUNGAN PADA PT. BNI SYARIAH CABANG DINOYO KOTA MALANG - Rabti Silmy; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
Economic activity is something that cannot be avoided anymore because humans as social creatures cannot do it themselves to fulfill their daily needs, so they need to make economic transactions with other individuals to support their business activities. However, increasing business is not always balanced with capability. However, efforts to increase business volume and productivity will certainly require support from the banking sector to support its funding. This research aims to determine the application of the syariah accounting for the profit sharing system in the savings program at PT BNI Syariah Dinoyo branch, Malang City. The data collection methods used are interview and documentation methods. An informant who is interviewed has important and needed information about an object. The informants associated with this research are managers and customers. The data analysis technique used in analyzing the data used descriptive qualitative analysis techniques. The result of this research is the implementation of the mudharabah system using revenue sharing and it is seen that so far PT Bank BNI Syariah has implemented the rules according to the DSN fatwa.Keywords: Application of Islamic accounting, profit sharing system, savings program.